Oxford Handbooks Online 2011
DOI: 10.1093/oxfordhb/9780195388947.013.0044
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Music: Tuning Composition to the Sounds of Science

Abstract: the oxford handbook of sound studies composition performed or recorded under water in settings ranging from swimming pools to the ocean, with playback unfolding above water or beneath. Composers of underwater music are especially curious about scientifi c accounts of how sound behaves in water and eager to acquire technologies of subaqueous sound production. We can learn much about how the underwater domain has been made sonically perceptible by attending to how composers adapt their practice to scientifi c la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Confronted with novel sounds during an era of social and ecological uncertainty, environmentalists learned to “shift the resonance of the tonalities” they received, finding new sources of meaning and self-understanding (Shank, 2014: 8). The theory of ideology help us understand how quickly these shifts can transpire, shifts wherein “shrieks” and “screams” become “ecologically tuned in arias” in accordance with new historical movements (Helmreich, 2012: 156).…”
Section: Resultsmentioning
confidence: 99%
“…Confronted with novel sounds during an era of social and ecological uncertainty, environmentalists learned to “shift the resonance of the tonalities” they received, finding new sources of meaning and self-understanding (Shank, 2014: 8). The theory of ideology help us understand how quickly these shifts can transpire, shifts wherein “shrieks” and “screams” become “ecologically tuned in arias” in accordance with new historical movements (Helmreich, 2012: 156).…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have suggested that oceanic and river environments are acoustically under threat. Helmreich (2011) and Stocker (2002) argue that oil drilling, factory fishing, and pleasure boating produce anthropogenic noise, sounds caused by humans (Pijanowski et al, 2011), which they counter, must affect marine life. Stocker has highlighted the biological importance of sounds produced by underwater creatures, suggesting that sounds produced by various underwater life forms are necessary to their survival.…”
Section: Renewable Technologies: the Sound Of Nature Harnessedmentioning
confidence: 99%
“…these steps toward the sonic city would not only enhance city life by helping to overcome the stress and anonymity of today's visual city, but would be one meas- ure for developing the sensory awareness of city residents and would provide an environment more responsive to human action and purpose. 22 Stefan Helmreich (2011) has argued that the very idea of soundscape -in the Schaferian sense of »an auditory environment« owes a debt to the »stereophonic space of recorded sound«, and one can find it in the conceptual field in which soundscape originally operated. In soundscape there is a bit of a phenomenological contradiction: while the concept is designed to get people to appreciate the sounds of both natural and built environments, to confront the world as it is, the concept demands that the listener relate to the world as if it is a recording or composition -in short, as a work -but a work that is also its own means of conveyance.…”
Section: The Emergence Of Soundscape As a Total Social Conceptmentioning
confidence: 99%